DevOps-Driven Infrastructure Management in Elementary Schools: A Sustainable Approach - Denny Jean Cross Sihombing (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
Effective infrastructure management in elementary schools is vital to supporting quality education. This includes managing the physical facilities, technology, and human resources that support learning. However, many elementary schools need help managing their infrastructure, including a shortage of physical and technological resources, inadequate maintenance, as well as a lack of long-term planning. This research uses a DevOps approach to develop a primary school infrastructure management application. It involves planning, analysis, development, testing, and evaluation. DevOps automates the development and testing process, ensuring the application can run sustainably and securely. Testing involves application feature testing, performance testing, and security testing. The results of this research include the development of a responsive application with an easy-to-use user interface. Automating the development and testing process improved the efficiency and quality of the software. Performance testing shows that the application can handle high loads. Security tests identify and fix potential vulnerabilities. Periodic evaluations and user feedback helped identify areas of improvement, including performance, security, and user interface response. The results of this research include the development of a responsive application with an easy-to-use user interface. Automation of development and testing processes improved efficiency and software quality. Performance testing showed that the application could handle high loads. Security tests identified and fixed potential vulnerabilities. Periodic evaluations and user feedback helped identify areas of improvement, including performance, security, and user interface response.